1985
DOI: 10.1002/jnr.490130404
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of anterior pituitary dopamine receptors by estradiol 17‐β: Dose‐response relationship

Abstract: Exposure of ovariectomized rats to estradiol-17-beta for 48-96 hr resulted in a dose-dependent reduction in the number but not the Kd of D-2 dopamine receptors of the anterior pituitary. No influence of estrogen was observed on dopamine or muscarinic acetylcholine receptors of caudate or hypothalamus. The dose-response relationship observed suggested that the influence of estrogen is directly on the pituitary, not secondary to the alteration of dopaminergic systems in the hypothalamus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…The latter observation is in agreement with the report that transplanted cells are more sensitive to secretagogues (24) and because DA is more effective inhibiting newly synthetized PRL (25). The data obtained from in vitro responsiveness of PRL to DA of in situ pituitaries from sham-operated animals, previously treated with CyA, suggests that changes induced in plasma oestradiol levels as were shown previously (5) may be involved in the the drug effects on the pituitary, changing the number of receptors for DA on the lactotrophs (26,27,28). Therefore, the previous endocrine milieu, induced by the treatment with CyA, directly influences the in vitro pituitary responsiveness to external stimuli as was described previously (29).…”
Section: Discussionsupporting
confidence: 91%
“…The latter observation is in agreement with the report that transplanted cells are more sensitive to secretagogues (24) and because DA is more effective inhibiting newly synthetized PRL (25). The data obtained from in vitro responsiveness of PRL to DA of in situ pituitaries from sham-operated animals, previously treated with CyA, suggests that changes induced in plasma oestradiol levels as were shown previously (5) may be involved in the the drug effects on the pituitary, changing the number of receptors for DA on the lactotrophs (26,27,28). Therefore, the previous endocrine milieu, induced by the treatment with CyA, directly influences the in vitro pituitary responsiveness to external stimuli as was described previously (29).…”
Section: Discussionsupporting
confidence: 91%
“…Acute effects of 178estradiol have also been shown in GH, cells (31,32). The present results, obtained by perifusion and RHPA cannot preclude the possibility of short-term effects by 178-estradio1, and what is more they contradict other reports which indicate that 48 h treatment is necessary to show the effects of 17P-estradiol (30). However, it has been shown that estrogen acts in different tissues with varying latencies ranging from seconds and minutes to hours and days (33), and it is unlikely that a single mechanism of action is involved.…”
Section: Discussioncontrasting
confidence: 79%
“…Consequently, a certain number of cells which may be sensitive to DA could possibly have previously liberated sufficient hormone to be classed as large plaque-forming cells, and thus falsify the data. 178-estradiol effects on DA receptors in lactotrophs from ovariectomized female rats have been shown to have different times of action; acute (several minutes) (6) or chronic (several hours) (30). Acute effects of 178estradiol have also been shown in GH, cells (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of ovariectomized rats, both E2 and P4 negatively influenced the activity of neuroendocrine dopaminergic neurons and increased prolactin secretion [19]. E2 has also been shown to decrease the number of dopamine receptors in the anterior pituitary [20,21]. Cloned prolactin-producing GH3 cells also have E2 and P4 receptors [22], and GH3 cell function was shown to be modulated by these steroids.…”
Section: Discussionmentioning
confidence: 99%